Bacterial adhesion properties of parylene C and D deposited on polydimethylsiloxane. (19th April 2022) - Han, Bing; Wang, He; Bing, Wei; Jin, Huichao
Abstract : Bacterial adhesion properties of parylene C and D coated polydimethylsiloxane were investigated in this study. Abstract : Parylene, a widely used protective coating, has received significant attention in medical applications. In this study, the bacterial adhesion properties of parylene C and D coated on polydimethylsiloxane (PDMS) substrates, labeled PCP and PDP, respectively, were investigated. The results showed that PCP and PDP had hydrophobic surfaces, and both parylene-coated PDMS surfaces had higher roughness than pristine PDMS. Bacterial adhesion assays against the Gram-negative bacteria Escherichia coli and Gram-positive bacteria Bacillus subtilis revealed that PCP was capable of reducing bacterial adhesion, whereas PDP had limited anti-adhesion capability. The anti-adhesion capability of PCP against bacteria was mainly because of its appropriate roughness and surface chemical composition, whereas that of PDP was limited by its unsuitable surface free energy. The results of this study suggest that parylene C has the potential to prevent early bacterial infections, whereas parylene D displays limited potential for the same under the conditions tested.